Occurrence of antibiotic resistant bacteria in pond water associated with integrated poultry-fish farming in Bangladesh - Farzana Ashrafi Neela,; Nasrin Akhter Banu, MST; Atiqur Rahman, MD; Habibur Rahman, M.; Firoz Alam, M. (Universiti Kebangsaan Malaysia, 2015)
The use of antibiotics in poultry feed can cause antibiotic resistance in integrated poultry-fish farming pond environment. Therefore, the goal of this study was to monitor the prevalence of drug-resistant bacteria in pond water associated with poultry-fish farming in Bangladesh. The results showed that the prevalence rate of tetracycline (TC) and ampicillin (AMP) resistant bacteria were 0.24 to 2.59% and 0.16 to 1.0%, respectively. The higher prevalence rate of TC and AMP-resistant bacteria was found in site 3 followed by site 4 and 2 compared with control site 1. Site 2, 3 and 4 were adjacent to the integrated poultry farm. On the other hand, higher TC and AMP-resistant bacteria were found in the rainy season than in the winter. The minimum inhibitory concentration result showed quite high level of TC and AMP-resistant bacterial distribution in the pond water. Seven genera of resistant bacteri¡a were identified in pond water samples by 16S rRNA gene analysis. Among them Acinetobacter sp. was predominant followed by Enterococcus sp., Pseudomonas sp., Bacillus, Staphylococcus sp., Enterobacter sp. and Brevibacillus sp.